Two new Aggregata species (Apicomplexa: Aggregatidae) infecting Octopus tehuelchus and Enteroctopus megalocyathus (Mollusca: Octopodidae) in Patagonia, Argentina - Sardella, Norma Haydee (2000)
During a long-term study carried out between 1981 and 1996 on the biological and fishery aspects of octopuses inhabiting the Gulfs of San Matías, San José, and Nuevo, Patagonia, Argentina, 2 new species of Aggregata (Apicomplexa: Aggregatidae) were found in the digestive tracts of Octopus tehuelchus d'Orbigny, 1834 (prevalence 72%) and Enteroctopus megalocyathus (Gould, 1852) (prevalence 77%). Both species can be distinguished from other congeners on the basis of their hosts, the diameters of sporocysts, and number and length of sporozoites. Despite overlap in the distributions of the two hosts species in the area covered in this study, both Aggregata new species exhibited high host specificity.